BLEEDING WHEN WEARING INTRAUTERINE CONTRACEPTIVES AND THEIR RELATIONSHIP WITH THE NITRIC OXIDE SYSTEM (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
There is a decrease in HIF-1α in women with IUDs, with the most profound differences found 6, 12 and 36 months after insertion of the IUD;  it was revealed that the decrease in HIF-1α reflects the state of women’s adaptability to the conditions of formation of long-term adaptation to the IUD; in women with high levels of HIF-1α (from 170% to 185%), adaptability to the IUD was manifested by the absence of clinical complaints about wearing a copper-containing contraceptive, and they did not experience complications associated with wearing the IUD. The absence of inflammation and bleeding in women with a high content of HIF-1α is apparently due to the tolerance of the vessels of the uterus and its mucous membrane to the IUD; patients with low levels of HIF-1α (from 120% to 140%) had the highest incidence of complications associated with wearing an IUD.